The Ethics of Intensification
XII, 231 p.
Keywords: This volume was written in response to the Food and Agriculture Organization (FAO) Series of Ethics Papers that broached a series of previously neglected issues in international agricultural development. The volume contains a diverse collection of highly respected international scholars offering comments and elaboration on the FAO papers on the ethics of agricultural intensification and on intensification in animal agriculture. The full text of the FAO intensification paper is followed by chapters that mount specific reactions to its relevance for agricultural technology, environmental protection, globalization and animal welfare, and these four topics are further discussed, debated and elaborated by eight commentary chapters. Questions of agricultural development policy are addressed in terms of the relevance to farmers, consumers and other interested parties, as well as from key disciplinary and philosophical approaches. The rationale and purpose behind the FAO papers is explained and suggestions are offered on how to make ethics more central to programming and planning for agricultural development projects.